Elastomeric pump malfunction resulting in over-infusion of local anesthetic. (January 2019) - Koogler, Andrew; Amusa, Ganiyu; Kushelev, Michael; Lawrence, Alec; Carlson, Laurah; Moran, Kenneth
A 70 year-old female patient presented for a right humeral head replacement. Preoperatively an interscalene catheter was placed and postoperatively connected to an elastomeric pump for continuous infusion at 8 mL/h of Ropivacaine 0.2% with an additional 5 mL patient activated bolus available every 30 min. About 17 h after the elastomeric pump was connected to the catheter, the 550 mL reservoir was found to be empty, indicating the pump's infusion rate was more than 32 mL/h despite the pump still being set at an infusion rate of 8 mL/h with a possible 5 mL bolus every 30 min. There was no visible damage or leak in the pump system, and the insertion site was dry. The patient denied any changes to the pump settings. She was alert and oriented and denied any signs of local anesthetic toxicity. The catheter was immediately pulled and the manufacturer notified. The manufacturer found a red tab broken inside the patient-controlled bolus remote resulting in the over-infusion. Despite the dependability of elastomeric pumps, healthcare providers must be aware of their possible complications and malfunctions.